2008
DOI: 10.1590/s1516-35982008000200024
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de cana-de-açúcar comparada a fontes tradicionais de volumosos suplementares no desempenho de vacas de alta produção

Abstract: O experimento foi conduzido com o objetivo de avaliar o desempenho de animais de alta produção alimentados com rações com diferentes fontes de volumosos. Foram availados os seguintes tratamentos: cana-de-açúcar in natura (CA); silagem de cana-de-açúcar inoculada com L. buchneri (SCA); silagem de milho (SM); e mistura de cana-de-açúcar in natura e silagem de milho (CASM). O experimento foi conduzido em quadrado latino 4×4 com períodos de 21 dias, de modo que, nos sete últimos dias, realizou-se a coleta de amost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
14

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 13 publications
0
5
0
14
Order By: Relevance
“…According to Nússio and Scmidt (2005), an earlier study, reducing alcohol accumulation improves animal performance due to an increase in DMI, as a result of improved palatability to bovine. Therefore, the silage of sugarcane may result in a better animal performance when the fermentation is controlled (Queiroz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to Nússio and Scmidt (2005), an earlier study, reducing alcohol accumulation improves animal performance due to an increase in DMI, as a result of improved palatability to bovine. Therefore, the silage of sugarcane may result in a better animal performance when the fermentation is controlled (Queiroz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies have indicated that when fermentation is controlled, the use of sugarcane in well-balanced diets provides satisfactory results in animal production (Pedroso et al, 2006;Queiroz et al, 2008;Mendes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, diferentes níveis de inclusão de forragens na ração podem resultar em variações no desempenho animal (Queiroz et al, 2008). Entretanto, desde que os parâmetros nutritivos (PB, energia e FDN) sejam ajustados para serem semelhantes ou muito próximos, como no presente estudo, espera-se que não haja diferenças no CMS e no ganho de peso, independente da fonte de forragem.…”
Section: Resultsunclassified